Children’s rights in relation to perceived parenting styles and parental well-being - Yetgen, Aylin. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
Research shows that human rights attitude in general is influenced by parental behavior from childhood and also from current well-being. The objective of this study was to investigate the mediating effect of current well-being on the relationship between perceived parental attitude and current well-being. The sample of this study were 252 Turkish parents with a child aged between 5 to 13 (M = 8.24, SD = 2.49). 155 (61.5%) female and 97 (38.5%) male parents voluntarily participated in this study. The participants were administered Demographic Information Form, Turkish Adaptation of Warwick- Edinburgh Mental Well-Being Scale, Parenting Styles Questionnaire, and Scale of Attitude towards Child Rights. Mediation models were computed by using SPSS 29 and PROCESS Macro 4 software. To investigate the subject further, a series of correlation and regression analysis were performed as well as a series of t-test and ANOVA to assess group differences. Results revealed that well-being had a partially mediating role in the relationship between three perceived parental attitudes (maternal acceptance, maternal strictness, paternal strictness) and children’s rights attitude. Relevant implications and future research directions are discussed in light of the findings.
Keywords: Children's rights.; Attachment behavior in children.; Parenting.